1989
DOI: 10.1002/ijc.2910430533
|View full text |Cite
|
Sign up to set email alerts
|

A carcinoembryonic antigen‐directed immunotoxin built by linking a monoclonal antibody to a hemolytic toxin

Abstract: Hybrid molecules prepared by linking toxins to monoclonal antibodies (MAbs) are cytotoxic to cells bearing the target antigen. The toxin most widely used has been the plant toxin ricin as the toxic component, which inhibits protein synthesis at the ribosome level. Immunotoxins based on membrane-active, hemolytic toxins can be a useful alternative when directed towards antigens which do not mediate internalization, as is the case for most carcinoma antigens. We present an alternative for toxic components using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 15 publications
1
23
0
1
Order By: Relevance
“…The results shown in Table 1 indicated that RTX-A demonstrated potent cytotoxic activity (IC 50 = 1–5 nM) against human caner cell lines, including HL-60, MDA-MB-231, HeLa, THP-1, and SNU-C4. The active concentrations of RTX-A, 10 −9 M, agree with the values of the cytotoxicity obtained earlier for the α-PFT of the actinoporin family, ranging from 10 −10 to 10 −7 M, according to reviewed data (Alvarez et al, 2009; Avila et al, 1988; Avila et al, 1989; Tejuca et al, 2004). …”
Section: Resultssupporting
confidence: 88%
“…The results shown in Table 1 indicated that RTX-A demonstrated potent cytotoxic activity (IC 50 = 1–5 nM) against human caner cell lines, including HL-60, MDA-MB-231, HeLa, THP-1, and SNU-C4. The active concentrations of RTX-A, 10 −9 M, agree with the values of the cytotoxicity obtained earlier for the α-PFT of the actinoporin family, ranging from 10 −10 to 10 −7 M, according to reviewed data (Alvarez et al, 2009; Avila et al, 1988; Avila et al, 1989; Tejuca et al, 2004). …”
Section: Resultssupporting
confidence: 88%
“…Indeed, the potency and properties of these cytolysins have prompted their evaluation as the toxic component of chimeric proteins targeted at tumour cells 8,9 and human parasites. 10 The nature of their interaction with lipids in bilayer membranes and the specific role of sphingomyelin in pore formation are not understood at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Actinoporins have been used to elucidate cell membrane dynamics and to investigate pharmaceutically relevant biomedical applications [21,22,23,24]. Several residues have been manipulated to identify functionally important regions within the protein [25], revealing an aromatic-rich region that forms the phosphocholine (POC) binding site, with a single amino acid residue (W112 in Equinatoxin II (EqII)) taking on a key role in initiating sphingomyelin recognition and pore formation [11,26,27].…”
Section: Introductionmentioning
confidence: 99%